DEVELOPMENT AND SENSORY EVALUATION OF IRON FORTIFIED RTE (READY TO EAT) EXTRUDED SNACK - N. KRISHNAIAH, GANESH V. BHAT, APARNA KUNA, K. MANORAMA and (The Journal of Research, PJTSAU, 2019)
Iron is essential for a wide range of functions in the human body. In addition to its major functions in oxygen transport and as a cofactor in many enzymes, iron also plays an important role in the immune system. Although the mechanisms involved are complex, there is good evidence that an abnormal iron nutritional status can lead to impaired immune function, with serious consequences for health (Allen et al. 2006).